2009
DOI: 10.1016/j.vaccine.2009.09.024
|View full text |Cite
|
Sign up to set email alerts
|

A robust lentiviral pseudotype neutralisation assay for in-field serosurveillance of rabies and lyssaviruses in Africa

Abstract: The inflexibility of existing serological techniques for detection of rabies in surveillance constrains the benefit to be gained from many current control strategies. We analysed 304 serum samples from Tanzanian dogs for the detection of rabies antibodies in a pseudotype assay using lentiviral vectors bearing the CVS-11 envelope glycoprotein. Compared with the widely used gold standard fluorescent antibody virus neutralisation assay, a specificity of 100% and sensitivity of 94.4% with a strong correlation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 32 publications
0
49
0
Order By: Relevance
“…These include Ebola virus (Wool-Lewis and Bates, 1998; Ito et al, 2001), hepatitis C (Bartosch et al, 2003; Hsu et al, 2003), SARS coronavirus (Nie et al, 2004; Temperton et al, 2005), rabies and lyssaviruses (Wright et al, 2008; 2009; 2010) as well as avian influenza viruses (Temperton et al, 2007). In contrast to the native viruses, their pseudotype counterparts can be handled in BSL1/2 facilities.…”
Section: Discussionmentioning
confidence: 99%
“…These include Ebola virus (Wool-Lewis and Bates, 1998; Ito et al, 2001), hepatitis C (Bartosch et al, 2003; Hsu et al, 2003), SARS coronavirus (Nie et al, 2004; Temperton et al, 2005), rabies and lyssaviruses (Wright et al, 2008; 2009; 2010) as well as avian influenza viruses (Temperton et al, 2007). In contrast to the native viruses, their pseudotype counterparts can be handled in BSL1/2 facilities.…”
Section: Discussionmentioning
confidence: 99%
“…This system has been used to study the entry pathways of a range of viruses, including human immunodeficiency virus (HIV), hepatitis C virus (HCV), pathogenic avian influenza and Ebola, offering a rapid and reproducible analysis of the viral glycoprotein-receptor interactions (Moller-Tank & Maury, 2015;Temperton et al, 2007;Wright et al, 2009;Zimmer et al, 2014). Previous reports showed that lentiviral HBVpps were infectious for human hepatocytes; however, given the limited knowledge of internalization pathways at the time, the receptor dependency was not studied (Chai et al, 2007;Sung & Lai, 2002).…”
mentioning
confidence: 99%
“…The HBV surface glycoprotein is unlike other viral glycoproteins tested to date (Moller-Tank & Maury, 2015;Temperton et al, 2007;Wright et al, 2009;Zimmer et al, 2014) in its failure to produce infectious pseudoparticles in human embryonal kidney cells (293T), requiring a liver cell background for infectious particles genesis. Our results show that whilst NTCP does play an essential role in HBVpp entry, it is unlikely to be the sole receptor facilitating infection.…”
mentioning
confidence: 99%
“…"Advantageous"qualities"of" 243" the"PVNA"platform"include"the"ability"to"conduct"the"assay"in"BSLS1"laboratories,"as"well"as"the" 244" availability"to"perform"multiplex"assays"and"incorporate"'lowScost'"reporter"genes"into" 245" pseudoparticles,"which"all"reduce"the"cost"implications"and"increase"the"potential"ubiquity"of" 246" pseudotyping" (Wright"et"al.,"2009(Wright"et"al.," ,"2010"Kaku"et"al.,"2012). ""However,"the"current"necessity"to"store" 247" aliquots"of"PV"supernatant"at"S80°C"and"to"maintain"the"coldSchain"during"PV"transportation"present" 248" serious"monetary"obstacles"for"laboratories"to"acquire"such"reagents,"especially"if"on"a"limited" 249" budget.""…”
mentioning
confidence: 99%